2021
DOI: 10.1590/1980-549720210042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores sociodemográficos associados ao beber pesado no Brasil: análises transversais da Pesquisa Nacional de Saúde

Abstract: RESUMO: Objetivo: Este estudo teve o objetivo de caracterizar o hábito de beber pesado na população brasileira, utilizando os dados das duas edições da Pesquisa Nacional de Saúde 2013 e 2019. Métodos: O tamanho das amostras em 2013 e 2019 foi de 60.202 e 88.943 indivíduos de 18 anos ou mais, respectivamente. Foram estimadas as prevalências do hábito de beber pesado (definido por 8 ou mais doses por semana para as mulheres e 15 ou mais doses para os homens) e os intervalos de confiança por sexo, faixa etári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
1
1
1
Order By: Relevance
“…The present findings are partially in line with a recent report pooling data from eight Finnish cohorts, 24 which found negative mediated interactive effects of alcohol intake on the association between income and alcohol‐attributable mortality. Interestingly, a negative proportion for differential exposure was noted in this study, and such a divergence from the present findings could be attributed—besides the fact that the outcomes are distinct—to different societal vulnerability factors and drinking patterns when comparing Finland and Brazil 42–44 . Another study detected a minimal attenuation in the effects of socioeconomic inequalities in alcohol‐related disorders after adjusting for the amount of alcohol use, using traditional mediation analysis in a Swedish cohort 26 .…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The present findings are partially in line with a recent report pooling data from eight Finnish cohorts, 24 which found negative mediated interactive effects of alcohol intake on the association between income and alcohol‐attributable mortality. Interestingly, a negative proportion for differential exposure was noted in this study, and such a divergence from the present findings could be attributed—besides the fact that the outcomes are distinct—to different societal vulnerability factors and drinking patterns when comparing Finland and Brazil 42–44 . Another study detected a minimal attenuation in the effects of socioeconomic inequalities in alcohol‐related disorders after adjusting for the amount of alcohol use, using traditional mediation analysis in a Swedish cohort 26 .…”
Section: Discussioncontrasting
confidence: 95%
“…Interestingly, a negative proportion for differential exposure was noted in this study, and such a divergence from the present findings could be attributedbesides the fact that the outcomes are distinct-to different societal vulnerability factors and drinking patterns when comparing Finland and Brazil. [42][43][44] Another study detected a minimal attenuation in the effects of socioeconomic inequalities in alcohol-related disorders after adjusting for the amount of alcohol use, using traditional mediation analysis in a Swedish cohort. 26 In some sort, this finding is equivalent to a negative total indirect effect, similar to what we found, although we were able to disentangle the contribution of each component of the mediated and interactive effects.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A mulher que é vista socialmente como bebedora leve é negligenciada e tem suas necessidades negadas, ao invés de obter medidas de cuidado -principalmente porque elas estão alcançando padrões compulsivos de consumo de bebida alcoólica tal qual os homens, conforme apresenta estudo realizado em Recife. 2,16,17 Destaca-se também que, em comparação aos homens, o consumo das mulheres tende a diminuir a partir dos 35 anos e aumentar com o avanço dos níveis de escolaridade. Concernente a isso, a idade foi apresentada como fator associado ao uso de álcool entre mulheres rurais.…”
Section: Discussionunclassified
“…[2][3][4] Consequently, tracking the patterns and prevalence of excessive alcohol consumption becomes pivotal in anticipating requirements for intervention and prevention, 5 as it fosters an understanding of the trajectory of intensified usage and facilitates the identification of high-risk populations. 6 One pattern of harmful alcohol consumption is heavy drinking (HD), which is characterized by frequent and excessive intake and has been used in epidemiological studies; 7 moreover, according to the WHO, it represents a multifaceted factor in various diseases, which resulted in 3 million global fatalities. 8 There is a scarcity of research specifically focused on HD in Latin America; nevertheless, studies can be found in countries such as Brazil, where 6.1% of the population exhibited patterns of excessive alcohol consumption in 2013, and 7.3% of citizens in 2019.…”
mentioning
confidence: 99%
“…8 There is a scarcity of research specifically focused on HD in Latin America; nevertheless, studies can be found in countries such as Brazil, where 6.1% of the population exhibited patterns of excessive alcohol consumption in 2013, and 7.3% of citizens in 2019. 7 It has been demonstrated that there are gender differences in alcohol consumption, 3 with women being more susceptible to the harms caused by alcohol consumption, while men have a higher probability of engaging in risky consumption (either heavy drinking or risky single occasion drinking). 9,10 Additionally, it has been observed that women reported diminished incidences of excessive episodic alcohol consumption during the pandemic.…”
mentioning
confidence: 99%